Selected moral values and their influence on financial decision making within the public sector: A case study of Poland - Salachna, Joanna M.; Szafranek, Anna; Tyniewicki, Marcin (Journal of Public Governance, 2018)
Objectives: The general aim of this article is to propose a theoretical model for the determinants of the optimal (required) operating of the public sector, including financial decision making in the scope of the creation of law and its application. At the same time, authors assert that universal moral values affect and should affect the legal system (including the creation and application of law governing public finances). Research Design & Methods: Precisely in the context of the values mentioned below, authors have decided to verify to what extent the mentioned model works in practice (an initial practical test). For this purpose two pilot studies have been conducted by use of the diagnostic poll method. Findings: Although in common (i.e. public) conviction decision making by public authorities (including decisions on public spending) should be based on moral values culturally accepted by society (which are often reflected in binding law), the results of the afore-mentioned studies were less than conclusive. Recommendations: The results underlined the need for in-depth interdisciplinary research (both legal and sociological), mainly into the moral aspects of legislating with regard to public finances, both at the state and local levels. Contribution: Research into the issue of the role of morality in financial decision making in Poland has not been undertaken yet. The authors created (and proposed) a theoretical model for the optimal operating of the public sector and decided to test the validity of the assumptions of the basic elements thereof by way of pilot studies. Article Classification: Research article JEL classification: A13, E62, H50, K40